2019
DOI: 10.2217/imt-2018-0105
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Shock Proteins in Diagnosis and Treatment: An Overview of Different Biochemical and Immunological Functions

Abstract: Heat-shock proteins (HSPs) have been involved in different functions including chaperone activity, protein folding, apoptosis, autophagy and immunity. The HSP families have powerful effects on the stimulation of innate immune responses through Toll-like receptors and scavenger receptors. Moreover, HSP-mediated phagocytosis directly enhances the processing and presentation of internalized antigens via the endocytic pathway in adaptive immune system. These properties of HSPs have been used for development of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 229 publications
1
35
0
Order By: Relevance
“…The third new result was that HSP60 was a novel antiviral protein against PRRSV replication (Figure ). It is known that HSP60 plays a significant role in chaperone activity and protein folding, and previous reports about the relationship between HSP60 and virus replication have shown that HSP60 could act as an important factor for viral replication . Here, we found that overexpression of HSP60 could inhibit PRRSV replication in MARC‐145 cells, and knockdown of HSP60 could promote PRRSV replication (Figure ), which indicated that HSP60 was an antiviral protein against PRRSV replication.…”
Section: Discussionsupporting
confidence: 60%
“…The third new result was that HSP60 was a novel antiviral protein against PRRSV replication (Figure ). It is known that HSP60 plays a significant role in chaperone activity and protein folding, and previous reports about the relationship between HSP60 and virus replication have shown that HSP60 could act as an important factor for viral replication . Here, we found that overexpression of HSP60 could inhibit PRRSV replication in MARC‐145 cells, and knockdown of HSP60 could promote PRRSV replication (Figure ), which indicated that HSP60 was an antiviral protein against PRRSV replication.…”
Section: Discussionsupporting
confidence: 60%
“…It is out of the scope of this review to give details on these pathophysiological situations. They are described in recent essays and compilations related to its involvement in infections, neurodegenerative diseases, cardiac diseases, stroke, metabolic diseases, cancer, asthma, aging and others [3,14,51,52,53]. Below we will focus our attention on immune disorders in which HSPA8 defaults have been described.…”
Section: Hspa8 and Immune Disordersmentioning
confidence: 99%
“…HSP protect cancer cells from environmental and pharmacological stress factors and can interfere with cancer therapy. Several studies have demonstrated the relationship between HSP and drug resistance, as well as the possibility of their use as biomarkers for detecting tumors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%